TLR4 Signaling in MPP+-Induced Activation of BV-2 Cells - Peng Zhou; Ruihui Weng; Zhaoyu Chen; Rui Wang; Jing Zou; Xu Liu; Jinchi Liao; Yanping Wang; Ying Xia; Qing Wang (Neural Plasticity)
Aims. This work was conducted to establish an in vitro Parkinson’s disease (PD) model by exposing BV-2 cells to 1-methyl-4-phenylpyridinium (MPP+) and exploring the roles of TLR2/TLR4/TLR9 in inflammatory responses to MPP+. Methods/Results. MTT assay showed that cell viability of BV-2 cells was 84.78 ± 0.86% and 81.18 ± 0.99% of the control after incubation with 0.1 mM MPP+ for 12 hours and 24 hours, respectively. Viability was not significantly different from the control group. With immunofluorescence technique, we found that MPP+ incubation at 0.1 mM for 12 hours was the best condition to activate BV-2 cells. In this condition, the levels of TNF-α, IL-1β, and iNOS protein were statistically increased compared to the control according to ELISA tests. Real time RT-PCR and western blot measurements showed that TLR4 was statistically increased after 0.1 mM MPP+ incubation for 12 hours. Furthermore, after siRNA interference of TLR4 mRNA, NF-κB activation and the levels of TNF-α, IL-1β, and iNOS were all statistically decreased in this cell model. Conclusion. MPP+ incubation at the concentration of 0.1 mM for 12 hours is the best condition to activate BV-2 cells for mimicking PD inflammation in BV-2 cells. TLR4 signalling plays a critical role in the activation of BV-2 cells and the induction of inflammation in this cell model.